PENGUJIAN KOEFISIEN ABSORBSI PADA PAPAN AKUSTIK MENGGUNAAN BAHAN DASAR BATANG JAGUNG DENGAN PEREKAT RESIN POLYESTER - Ayu Hardianti Mahmud; Ihsan Ihsan; Sahara Sahara (Universitas Islam Negeri Alauddin Makassar, 2020)
This study aims to determine the effect of thickness variations on the sound absorption coefficient of acoustic material from corn stalks. The study was conducted by making acoustic board samples from corn stems with Polyester Resin adhesive. In this study the thickness of the acoustic boards used were 0.7 cm, 1 cm, and 1.5 cm. The amount of frequency used is 250 Hz, 500 Hz, 1000 Hz, 2000 Hz. Based on the results of the research, the absorption coefficient value is proportional to the thickness, where the greater the thickness of a material, the lower the coefficient value produced. In the thickest sample with a thickness of 1.5 cm for a frequency of 250 Hz, the absorption coefficient value is 0.177, while at the frequency of 2000 Hz the absorption coefficient value is 0.084.